Potensi Serapan Karbon Inorganik pada Kawasan Karst Tropis di Karst Biduk-Biduk, Kalimantan Timur - Danardono Danardono; Eko Haryono; M Widyastuti (Jurnal Wilayah dan Lingkungan, 2022)
The increase in carbon emissions in Indonesia is a problem that needs to be mitigated. One of the ways is to make an inventory of areas that have the potential to absorb carbon. One of areas that has the potential to absorb inorganic carbon is the karst area through the karstification process. However, research on inorganic carbon sequestration in karst areas, especially in tropical karst areas, is rarely studied. This potential needs to be studied to determine the important role of karst areas in efforts to reduce global carbon emissions. This study aims to identify the potential value of inorganic carbon sequestration; in Biduk-Biduk Karst Area and this efforts to reduce carbon emissions in Indonesia. Inorganic carbon sequestration was calculated based on the dissolution rate of carbonate rocks using standard limestone tablets. The efforts of karst areas to reduce carbon emissions was modeled by comparing the total value of inorganic carbon sequestration in karst areas with the value of carbon emissions in Indonesia. The results showed that the potential of the Biduk-Biduk Tropical Karst to absorb inorganic carbon is 726.864 tons/year-CO2. Inorganic carbon uptake shows variation based on differences in surface morphology, where areas with flat slopes have a higher inorganic carbon sequestrationn. This value can help to reduce carbon emissions in East Kalimantan by 7.3% and Indonesia by 0.5%. Therefore, conservation of karst areas is important to do to support carbon emission reduction programs in Indonesia.